Academic Supervision of Independent Curriculum Implementation at Elementary School - Rini Budiwati; Anam Sutopo; Yulia Maftuhah Hidayati; Choiriyah Widyasari (STAI Hubbulwathan Duri, 2023)
This research aimed to examine academic supervision, including planning, implementing, and evaluating learning at a state elementary school in Kedungpilang, Wonosamodro, Boyolali. The respondents in this study were school principals, class 1 teachers, and class 4 teachers. The technique for selecting samples used purposive sampling, which is a method for sampling data sources with several considerations. The principal is implementing academic supervision for grade 1 teachers and grade 4 teachers, who have implemented the independent curriculum, while other classes are still using the 2013 curriculum. This research method is a qualitative phenomenology with a case study. The data were collected through observation, interviews, and documentation. Data analysis techniques used were flow, data reduction, and data presentation at the verification stage. Testing the validity of the data was carried out by using a triangulation approach. The academic supervision results for two teachers during the planning stage were both in the suitable category, with recap values of 86% and 89%, respectively. During the implementation stage, the class 1 teacher received a score of 86% in the excellent category, while the class 4 teacher achieved a score of 91% in the outstanding category. In the evaluation stage, both teachers were again in the excellent category, with recap scores of 86% and 85%, respectively.